Associations Between Heart Rate Recovery Dynamics With Estradiol Levels in 20 to 60 Year-Old Sedentary Women - Beltrame, Thomas; Catai, Aparecida M.; Rebelo, Ana C.; Tamburús, Nayara Y.; Zuttin, Roberta S.; Takahashi, Anielle C. de Medeiros; da Silva, Ester (Frontiers in Physiology, 2018)
It is hypothesized that estradiol levels, as well as aging, influence cardiac autonomic function in women. The main aim of this study was to test the correlations between heart rate recovery (HRR) dynamics as a proxy of cardiac autonomic function with estradiol levels and age in women. This cross-sectional study involved 44 healthy women. Heart rate (HR) data were obtained beat-by-beat during the entire experiment. Maximal incremental exercise testing (IET) on a cycle-ergometer was performed followed by 6 min of recovery. During the IET recovery period, the overall HRR dynamics were evaluated by exponential data modelling (time constant “τ”) where shorter τ indicates faster HRR adjustment. Considering the cardiac autonomic complexity, HRR dynamics were also evaluated by delta analysis considering different HR data intervals. The relationship between HRR dynamics, estradiol levels and age was tested by Pearson product-moment correlation. The overall HRR dynamics (i.e., τ) were statistically correlated with age (r = 0.58, p < 0.001) and estradiol levels (r = -0.37, p = 0.01). The delta analysis showed that the slower overall HRR associated with aging was a consequence of slower dynamics occurring within the 45-210 s interval, indicating slower sympathetic withdrawal. In conclusion, aging effects on HRR in women seems to be correlated with a slower sympathetic withdrawal. In addition, the cardioprotective effect previously associated with estradiol seems not to influence the autonomic modulation during exercise recovery periods in women.